Isolation, identification, cultivation and determination of antimicrobial β-glucan from a wild-termite mushroom Termitomyces heimii RFES 230662 - Rahayu Binti Ahmad; Srivani Sellathoroe; Tengku Shafazila Bt Tengku Saharuddin; Iffah Izzati Zakaria; Suguna Selvakumaran; Wan Abd Al Qadr Imad Wan-Mohtar; Ehwan Ngadi (Elsevier Ltd., 2024)
During the monsoon season, a wild-termite mushroom Termitomyces heimii RFES 230662 (THR2) was successfully isolated from Negeri Sembilan, Malaysia. The mushroom was morphologically labelled based on its stipe, pileus, and the budding mycelia from the termites nest. Genetic component of THR2 (300 bp) was sequenced and found to be 99% identical to Termitomyces sp. strain. The evolutionary distance (Knuc) of the isolate justified THR2 as T. heimii species. Two THR2 extracts were prepared from fruiting body (FB) and mycelial biomass (MB) for antimicrobial responses. THR2 was cultivated in a submerged-fermentation (SF) producing 8.55 g/L of MB, 0.80 g/L of endopolysaccharide (ENS) and 1.44 g/L of exopolysaccharide (EPS), respectively. For THR2-FB, two ENS extracts were obtained using hot (3.20 g/L) and cold-water (1.36 g/L) treatments. FTIR spectra analysis verified all polysaccharide as β-glucan when compared to laminarin standard. Those β-glucan possess antibacterial properties with highest response shown by ß-glucan-FB compared to ß-glucan-MB extracts. These findings serve as the blueprint for the production of β-glucan from a rare termite mushroom.